Enhanced synchronization in an array of spin torque nano-oscillators in the presence of oscillating external magnetic field. (21st January 2015) - Subash, B.; Chandrasekar, V. K.; Lakshmanan, M.
Abstract: We demonstrate that the synchronization of an array of electrically coupled spin torque nano-oscillators (STNO) modelled by Landau-Lifshitz-Gilbert-Slonczewski (LLGS) equation can be enhanced appreciably in the presence of a common external microwave magnetic field. The applied microwave magnetic field stabilizes and enhances the regions of synchronization in the frequency determining parameter space. We have identified two regions of synchronization in the parameter space of our analysis, where the oscillators are exhibiting synchronized oscillations thereby emitting improved microwave power. To characterize the synchronized oscillations we have calculated the locking range in the domain of external source frequency.